2018
DOI: 10.1063/1.5019058
|View full text |Cite
|
Sign up to set email alerts
|

Failure mode prediction for composite structural insulated panels with MgO board facings

Abstract: Abstract. Sandwich panels are readily used in civil engineering due to their high strength to weight ratio and the ease and speed of assembly. The idea of a sandwich section is to combine thin and durable facings with a light-weight core and the choice of materials used allows obtaining the desired behaviour. Panels in consideration consist of MgO (magnesium oxide) board facings and expanded polystyrene core and are characterized by immunity to biological corrosion, a high thermal insulation and a relatively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Zheng et al [36] built a chipboard structure from magnesium cement to test its mechanical strength, water resistance, thermal stability, and non-flammability. The results showed that this board had excellent properties.…”
Section: Flexing Static and Mechanical Propertiesmentioning
confidence: 99%
“…Zheng et al [36] built a chipboard structure from magnesium cement to test its mechanical strength, water resistance, thermal stability, and non-flammability. The results showed that this board had excellent properties.…”
Section: Flexing Static and Mechanical Propertiesmentioning
confidence: 99%
“…A literature study was also used to assume Poisson's ratios, υ [40,41], as well as angles of friction, β, and dilation angles, ψ [42,43]. More detailed reasoning behind the specified data can be found in research presented in [33][34][35]. The material description was developed further, as a part of the current study, with the addition of SSV value corresponding to the core shear stress-state in the elastic range.…”
Section: Materials Model Descriptionmentioning
confidence: 99%
“…It was noted that both EPS and MgO board exhibit distinctly different behavior in compression and tension in all ranges: elastic, plastic, and failure, indicating at the substantial influence of the material bimodularity. An initial FE solution incorporating material bimodularity effect was created and proved to capture CSIP flexural behavior quite well; however, it failed to predict the correct failure pattern in some cases [35]. It was determined that the correct prediction of failure initiation location strongly depends on (1) the accuracy of elastic core response in areas where stress-state transits from compression to shear (e.g.…”
Section: Introductionmentioning
confidence: 99%